Morgan-Voyce Polynomial Approach for Solution of High-Order Linear Differential-Difference Equations with Residual Error Estimation - Bengü TÜRKYILMAZ (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2016)
The main aim of this study is to apply the Morgan-Voyce polynomials for the solution of high-order linear differential difference equations with functional arguments under initial boundary conditions. The technique we have used is essentially based on the truncated Morgan-Voyce series and its matrix representations along with collocation points. Also, by using the Mean-Value Theorem and residual function, an efficient error estimation technique is proposed and some illustrative examples are presented to demonstrate the validity and applicability of the method.